Composite activator, manganese slag-red mud concrete and preparation method and application of manganese slag-red mud concrete
By using composite exciters to treat manganese slag and red mud, manganese slag-red mud concrete with excellent mechanical properties and durability is prepared, which solves the shortcomings in the treatment and utilization of these industrial solid waste materials in the prior art, and achieves efficient utilization of resources and environmental protection.
Patent Information
- Application Number
- CN202411900316.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to effectively treat and utilize electrolytic manganese slag and red mud, which leads to the occupation of land and polluting the environment, and the concrete used in its resource-based utilization has insufficient strength and durability.
Compound excitants, including mineral powder, lime, cement, nano calcium carbonate or nano silicon powder, as well as sodium silicate and sodium hydroxide, are used to improve the resource utilization effect of manganese slag and red mud, and manganese slag-red mud concrete with excellent mechanical properties and durability are prepared.
The harmless substances of manganese slag and red mud were cured and stabilized, and a new building material with a strength of more than C40 cement concrete was prepared, with good durability, in line with the concept of circular economy, and the high-value utilization of waste was achieved.
Smart Images

Figure BDA0005202977610000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of manganese slag-red mud resource utilization, and particularly relates to a composite activator, manganese slag-red mud concrete, and a preparation method and application thereof. Background Art
[0002] Industrial solid waste materials refer to various waste slag, dust and other wastes discharged by industrial and mining enterprises during their production activities, such as electrolytic manganese slag, blast furnace slag, fly ash, steel slag, red mud, industrial by-product gypsum, etc., mainly involving mining, chemical, thermal power, chemical fiber, foundry and mineral smelting industries.
[0003] As for the treatment of electrolytic manganese slag, electrolytic manganese production enterprises usually use wet stockpiling to pile up electrolytic manganese slag. This open-air stacking method not only occupies a large amount of land resources, but also the pollutants in the electrolytic manganese slag are very likely to pollute the surrounding water and soil, posing a great threat to the surrounding ecological environment. Red mud, as an industrial solid waste, is usually stored in the form of red mud slurry, or directly discharged into the nearby ocean through a pipeline. Since red mud contains a large amount of metal ions, fine particles, and high alkalinity (pH = 10-12.5), it is easy to cause groundwater and marine environmental pollution. The alkali liquid in red mud can also cause soil alkalization and swamping, causing serious soil pollution. In addition, the red mud content in the wet stockpiled red mud slurry is only 15-40%, and the stacking space is large. The dry stockpiled red mud, due to the fine red mud powder particles, may cause serious dust pollution, which seriously endangers human physical and mental health. At the same time, the stockpiling cost and management expenses of red mud are also very high, and enterprises are under great pressure.
[0004] At present, there are relevant studies on the resource processing of red mud and manganese slag, such as preparing them into concrete. However, the concrete prepared by them still has deficiencies in strength and durability, and cannot meet the demand for concrete performance in the construction field.
[0005] Therefore, it is of great significance to provide a method for resource utilization of red mud and manganese slag. Summary of the invention
[0006] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides a composite activator, which can treat manganese slag and red mud with the composite activator, not only to solidify and stabilize the harmful substances in the manganese slag and red mud waste, but also to prepare manganese slag-red mud concrete with excellent mechanical properties and durability, so as to realize the large-scale resource utilization of manganese slag and red mud.
[0007] The inventive concept of the present invention is as follows: the composite activator of the present invention comprises mineral powder, lime, cement, filler, and component A; the filler comprises at least one of nano calcium carbonate and nano silicon powder; the component A comprises sodium silicate and sodium hydroxide. The present invention adopts sodium silicate and sodium hydroxide as a compound, and adopts nano calcium carbonate or nano silicon powder as a filler, and combines mineral powder, lime, and cement. The components work together to improve the mechanical properties and durability of the concrete prepared after the reaction with red mud and manganese slag.
[0008] Among them, during the hydration process, C3S in cement is rapidly hydrolyzed to release Ca(OH)2. The added lime can dissolve Ca(OH)2 in the vitreous body and stimulate the activity of mineral powder and manganese slag. The addition of lime will also increase the supersaturation of Ca(OH)2, and Ca(OH)2 crystals will precipitate in advance, thereby shortening the induction period. C3A in the solution is rapidly hydrated, and in the presence of calcium sulfate, calcium aluminate is formed, which drives the consumption of iron and aluminum ions, and the number of crystals gradually increases. It is then converted into monosulfur hydrated calcium aluminum sulfate (ferrite). As the hydration products increase, the hydration products fill the space originally occupied by water to form a material with a certain strength.
[0009] The alkali in red mud is mixed with sodium silicate and sodium hydroxide in the composite activator, which increases the alkali concentration and thus improves the alkali activation ability, so that silicon and aluminum phases can be dissolved under alkaline conditions to form a complex system composed of silicates, aluminates and aluminosilicates. The dissolution rate of the amorphous silicon-aluminum phase is accelerated, resulting in a saturated state of aluminosilicates in the mixed solution. At this time, gelation reaction begins to appear in the system, forming a low-polymer gel, and gradually forms a network structure NSAH (sodium silicate-aluminate-hydrate) polymerization (geological polymerization) as the coagulation proceeds. This dense network structure can effectively disperse external forces and improve the overall compressive resistance of the material. The NASH gel phase has a high degree of chemical density and stability, can effectively prevent the intrusion and destruction of chemical media, and has impermeability and corrosion resistance.
[0010] In addition, the NASH gel phase generated during the reaction and the unreacted particles of calcium aluminate, nano-calcium carbonate / silica powder, calcium silicate hydrate (CSH), calcium hydroxide (CH), cement, and mineral powder fill each other's pores, further enhancing the density and strength of the material, making the strength exceed that of C40 cement concrete.
[0011] At the same time, the high iron content of red mud and the calcium sulfate in the manganese slag form ferroaluminite, which can improve the early and late strength, and has good resistance to sulfate corrosion, making the entire product have good durability.
[0012] The reaction equation involved is as follows:
[0013] 3CaO·SiO2+nH2O=xCaO·SiO2·yH2O+(3-x)Ca(OH)2;
[0014] 2CaO·SiO2+mH2O=xCaO·SiO2·yH2O+(2-x)Ca(OH)2;
[0015] 4CaO·Al2O3 ·13H2O+3(CaSO4·2H2O)+14H2O=3CaO·Al2O3 ·3CaSO4·32H2O +Ca(OH)2;
[0016] 3CaO·Al2O3·3CaSO4·32H2O+2(CaO·Al2O3·13H2O)=3(3CaO·Al2O3·CaSO4·12H2O)+
[0017] 2Ca(OH)2+20H2O;
[0018] 4CaO·Al2O3·Fe2O3+2Ca(OH)2+6(CaSO4·2H2O)+50H2O=2[4CaO·(Al2O3·Fe2O3)·3CaSO4·32H2O];
[0019] 2[4CaO·(Al2O3·Fe2O3)·13H2O]+4CaO·(Al2O3·Fe2O3)·3CaSO4·32H2O=3[3CaO·(Al2O3·Fe2O3)·CaSO4·12H2O]+2Ca(OH)2+20H2O.
[0020] The reaction equation for geopolymerization is:
[0021]
[0022] Therefore, a first aspect of the present invention provides a composite activator.
[0023] Specifically, the composite activator includes mineral powder, lime, cement, filler, and component A;
[0024] The filler includes at least one of nano calcium carbonate and nano silicon powder;
[0025] The A component includes sodium silicate and sodium hydroxide.
[0026] Preferably, in terms of mass percentage, the composite activator includes 37-75% mineral powder, 0.9-11% lime, 18-60% cement, 0.9-5.5% filler, and 0.9-4.5% component A.
[0027] Further preferably, in terms of mass percentage, the composite activator includes 40-70% mineral powder, 1-10% lime, 20-57% cement, 1-5% filler, and 1-4% component A.
[0028] Preferably, in the component A, the mass ratio of the sodium silicate to the sodium hydroxide is (6-8):3; further preferably, in the component A, the mass ratio of the sodium silicate to the sodium hydroxide is (6.5-7.5):3; further preferably, in the component A, the mass ratio of the sodium silicate to the sodium hydroxide is 7:3.
[0029] Preferably, the cement is selected from at least one of Portland cement, limestone cement and pozzolanic cement.
[0030] Specifically, the main components of the cement are 3CaO·SiO2 (C3S), 2CaO·SiO2 (C2S), 3CaO·Al2O3 (C3A), and 4CaO·Al2O3·Fe2O3 (C4AF), which function to increase the clinker mineral phase and have hydraulic properties.
[0031] Specifically, nano-calcium carbonate or silica powder can enhance the fluidity of particles, enhance plasticity in the early stage, and fill pores in the later stage, making the structure tighter and improving strength. In addition, nano-calcium carbonate or silica powder can provide crystal nuclei for CSH, CH and NSAH gels, so that CSH, CH and NSAH gels grow rapidly on the surface of nano-calcium carbonate or silica powder, accelerate hydration, and improve the density of cement. At the same time, nano-calcium carbonate or silica powder can also form calcium aluminum carbonate / calcium silicon carbonate with C3A, promoting the intergrowth of crystals and the development of cement strength.
[0032] The second aspect of the present invention provides a method for preparing the composite activator described in the first aspect of the present invention.
[0033] Specifically, the preparation method of the composite activator comprises the following steps:
[0034] Each component is taken to form the composite activator.
[0035] A third aspect of the present invention provides a manganese slag-red mud concrete.
[0036] Specifically, the raw materials for preparing the manganese slag-red mud concrete include red mud, manganese slag, the composite activator described in the first aspect of the present invention, gravel, sand and water.
[0037] Preferably, the manganese slag is electrolytic manganese slag.
[0038] Preferably, the stone is crushed stone, and the sand is river sand.
[0039] Preferably, the sum of the masses of the red mud, manganese slag and composite activator accounts for 14-25% of the total mass of the manganese slag-red mud concrete.
[0040] Further preferably, the sum of the masses of the red mud, manganese slag and composite activator accounts for 15-22% of the total mass of the manganese slag-red mud concrete.
[0041] Preferably, the mass of the gravel accounts for 40-60% of the total mass of the manganese slag-red mud concrete; further preferably, the mass of the gravel accounts for 45-55% of the total mass of the manganese slag-red mud concrete.
[0042] Preferably, the mass of the sand accounts for 18-33% of the total mass of the manganese slag-red mud concrete; further preferably, the mass of the sand accounts for 20-30% of the total mass of the manganese slag-red mud concrete.
[0043] Preferably, the mass of the water accounts for 5.5-8.5% of the total mass of the manganese slag-red mud concrete; further preferably, the mass of the water accounts for 6-8% of the total mass of the manganese slag-red mud concrete.
[0044] Preferably, the mass ratio of the red mud, manganese slag and composite activator is (3-5): 3: (2-4).
[0045] Further preferably, the mass ratio of the red mud, manganese slag and composite activator is (3.5-4.5): 3: (2.5-3.5).
[0046] More preferably, the mass ratio of the red mud, manganese slag and composite activator is 4:3:3.
[0047] Preferably, the stones include stones with a particle size of 5-10 mm and stones with a particle size greater than 10 mm and less than or equal to 25 mm.
[0048] Preferably, among the stones, the mass proportion of stones with a particle size of 5-10 mm is 25-75%, and the mass proportion of stones with a particle size greater than 10 mm and less than or equal to 25 mm is 25-75%.
[0049] Further preferably, among the stones, the mass of stones with a particle size of 5-10 mm accounts for 30-70%, and the mass of stones with a particle size greater than 10 mm and less than or equal to 25 mm accounts for 30-70%.
[0050] The fourth aspect of the present invention provides a method for preparing the manganese slag-red mud concrete described in the third aspect of the present invention.
[0051] Specifically, the method for preparing the manganese slag-red mud concrete comprises the following steps:
[0052] (1) mixing the red mud, manganese slag and composite activator to obtain a mixed powder;
[0053] (2) Mixing the mixed powder obtained in step (1) with the gravel, sand and water to obtain the manganese slag-red mud concrete.
[0054] Preferably, step (2) specifically comprises mixing the mixed powder obtained in step (1) with gravel and sand, and then adding water to obtain the manganese slag-red mud concrete.
[0055] The fifth aspect of the present invention provides an application of the composite activator described in the first aspect of the present invention or the manganese slag-red mud concrete described in the third aspect of the present invention in the resource utilization of manganese slag and red mud.
[0056] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0057] (1) The present invention adopts sodium silicate and sodium hydroxide as a compound, and adopts nano calcium carbonate or nano silicon powder as a filler, combined with mineral powder, lime and cement. The components work together to improve the mechanical properties and durability of the concrete prepared after the reaction with red mud and manganese slag.
[0058] (2) By mixing red mud and manganese slag in appropriate proportions, the two solid waste elements complement each other and form polymer ferroaluminite, hydrated calcium silicate, and sodium aluminoferrite gel polymer under the action of a composite activator. This not only solidifies and stabilizes the harmful substances in these wastes, but also prepares a new type of building material with excellent mechanical properties. Its 28-day strength exceeds that of C40 concrete and has good durability.
[0059] (3) The red mud and manganese slag resource treatment method of the present invention not only conforms to the concept of circular economy, but also can realize the high-value utilization of waste and improve resource utilization efficiency, thereby achieving the dual goals of environmental protection and resource conservation. DETAILED DESCRIPTION
[0060] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0061] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0062] The source information of the relevant raw material components in the embodiments and application examples of the present invention is as follows:
[0063] The mineral powder comes from Guangdong Shaoguan Iron and Steel Jiayang New Materials Co., Ltd. It is made by grinding the slag from Shaoguan Iron and Steel's blast furnace. Its main chemical components are silicon dioxide, aluminum oxide, calcium oxide, and iron oxide.
[0064] The lime comes from the roasting kiln of Shaoguan Iron and Steel Co., Ltd., with a purity of 89% and the main impurity being calcium carbonate.
[0065] Red mud comes from Guangxi Apple Aluminum Company of China Aluminum Corporation. Its main chemical components are: SiO2, CaO, Fe2O3 and Al2O3, and caustic soda.
[0066] Electrolytic manganese slag comes from Guangxi Dameng Group. The main chemical components of electrolytic manganese slag are SiO2, CaO, SO3 and Al2O3, followed by a small amount of Fe2O3, MgO and MnO. The untreated electrolytic manganese slag has a high natural moisture content, and the moisture content measured in the laboratory is 26%.
[0067] Example 1
[0068] A composite activator comprises, by mass percentage, 55% of mineral powder, 35% of silicate cement, 5% of lime, 3% of nano calcium carbonate, 2% of sodium silicate and sodium hydroxide (the mass ratio of sodium silicate to sodium hydroxide is 7:3).
[0069] A method for preparing a composite activator comprises the following steps:
[0070] Take mineral powder, lime, silicate cement, nano calcium carbonate, sodium silicate and sodium hydroxide to form a composite activator.
[0071] Example 2
[0072] A composite activator comprises, by mass percentage, 50% of mineral powder, 35% of silicate cement, 6% of lime, 5% of nano calcium carbonate, 4% of sodium silicate and sodium hydroxide (the mass ratio of sodium silicate to sodium hydroxide is 7:3).
[0073] A method for preparing a composite activator comprises the following steps:
[0074] Take mineral powder, lime, silicate cement, nano calcium carbonate, sodium silicate and sodium hydroxide to form a composite activator.
[0075] Example 3
[0076] A composite activator, calculated by mass percentage, includes 65% mineral powder, 25% silicate cement, 5% lime, 3% nano silicon powder, 2% sodium silicate and sodium hydroxide (the mass ratio of sodium silicate to sodium hydroxide is 7:3).
[0077] A method for preparing a composite activator comprises the following steps:
[0078] Take mineral powder, lime, silicate cement, nano silicon powder, sodium silicate and sodium hydroxide to form a composite activator.
[0079] Application Example 1
[0080] A manganese slag-red mud concrete, wherein the raw materials for preparing the concrete include red mud, manganese slag, crushed stone, river sand, the composite activator of Example 1 and water;
[0081] The sum of the masses of red mud, manganese slag and the composite activator of Example 1 is 17.35% of the total mass of the manganese slag-red mud concrete, and the mass ratio of red mud, manganese slag and composite activator powder is 4: 3: 3;
[0082] The amount of crushed stone accounts for 49.32% of the total mass of manganese slag-red mud concrete. Among the crushed stones, 5-10mm crushed stones account for 50% of the total crushed stones, and crushed stones greater than 10mm and less than or equal to 25mm account for 50% of the total crushed stones;
[0083] The amount of river sand accounts for 26.56% of the total mass of manganese slag-red mud concrete, and the amount of water accounts for 6.77% of the total mass of manganese slag-red mud concrete.
[0084] A method for preparing manganese slag-red mud concrete comprises the following steps:
[0085] (1) red mud, manganese slag and the composite activator of Example 1 are mixed to obtain a mixed powder;
[0086] (2) Add crushed stone and river sand to the mixed powder obtained in step (1), premix for 5 minutes and then add water to obtain manganese slag-red mud concrete.
[0087] Application Example 2
[0088] The difference between Application Example 2 and Application Example 1 is that Application Example 2 uses the composite activator of Example 2, and the rest is the same as Application Example 1.
[0089] Application Example 3
[0090] The difference between Application Example 3 and Application Example 1 is that Application Example 3 uses the composite activator of Example 3, and the rest is the same as Application Example 1.
[0091] Application Example 4
[0092] The only difference between Application Example 4 and Application Example 1 is that in Application Example 4, the mass ratio of red mud, manganese slag and composite activator is 3:3:4, and the rest is the same as Application Example 1.
[0093] Comparative Example 1
[0094] The difference between Comparative Example 1 and Example 1 is that the amount of mineral powder used in Comparative Example 1 is 35%, and the amount of silicate cement used in Comparative Example 1 is 55%. The rest is the same as Example 1.
[0095] Comparative Example 2
[0096] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not contain nano calcium carbonate, and the sum of the mass percentages of sodium silicate and sodium hydroxide is 5%. The rest is the same as Example 1.
[0097] Comparative Example 3
[0098] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses an equal amount of calcium hydroxide to replace sodium hydroxide, and the rest is the same as Example 1.
[0099] Comparative Example 4
[0100] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses an equal amount of mineral powder to replace sodium silicate and sodium hydroxide, that is, does not contain sodium silicate and sodium hydroxide, and the rest is the same as Example 1.
[0101] Comparative Example 5
[0102] The difference between Comparative Example 5 and Example 1 is that Comparative Example 5 uses an equal amount of mineral powder to replace nano-calcium carbonate, that is, does not contain nano-calcium carbonate, and the rest is the same as Example 1.
[0103] Comparative Example 6
[0104] The difference between Comparative Example 6 and Example 1 is that Comparative Example 6 uses an equal amount of mineral powder to replace lime, that is, does not contain lime, and the rest is the same as Example 1.
[0105] Comparative application example 1
[0106] The difference between Comparative Application Example 1 and Application Example 1 is that Comparative Application Example 1 uses the composite activator of Comparative Example 1, and the rest is the same as Application Example 1.
[0107] Comparative Application Example 2
[0108] The difference between Comparative Application Example 2 and Application Example 1 is that Comparative Application Example 2 uses the composite activator of Comparative Example 2, and the rest is the same as Application Example 1.
[0109] Comparative Application Example 3
[0110] The difference between Comparative Application Example 3 and Application Example 1 is that Comparative Application Example 3 uses the composite activator of Comparative Example 3, and the rest is the same as Application Example 1.
[0111] Comparative Application Example 4
[0112] The difference between Comparative Application Example 4 and Application Example 1 is that Comparative Application Example 4 uses the composite activator of Comparative Example 4, and the rest is the same as Application Example 1.
[0113] Comparative Application Example 5
[0114] The difference between Comparative Application Example 5 and Application Example 1 is that Comparative Application Example 5 uses the composite activator of Comparative Example 5, and the rest is the same as Application Example 1.
[0115] Comparative Application Example 6
[0116] The difference between Comparative Application Example 6 and Application Example 1 is that Comparative Application Example 6 uses the composite activator of Comparative Example 6, and the rest is the same as Application Example 1.
[0117] Comparative Application Example 7
[0118] The only difference between Comparative Application Example 7 and Application Example 1 is that in Comparative Application Example 7, the mass of the mixed powder accounts for 14.35% of the total mass of the manganese slag-red mud concrete, and the river sand accounts for 29.56% of the mass of the manganese slag-red mud concrete. The rest is the same as Application Example 1.
[0119] Comparative Application Example 8
[0120] The only difference between Comparative Application Example 8 and Application Example 1 is that in Comparative Application Example 8, the mass of the mixed powder accounts for 22.35% of the total mass of the manganese slag-red mud concrete, and the river sand accounts for 21.56% of the mass of the manganese slag-red mud concrete. The rest is the same as Application Example 1.
[0121] Comparative Application Example 9
[0122] The only difference between Comparative Application Example 9 and Application Example 1 is that in Comparative Application Example 9, river sand accounts for 23.56% of the mass of manganese slag-red mud concrete, and the mass of water accounts for 9.77% of the total mass of manganese slag-red mud concrete. The rest is the same as Application Example 1.
[0123] Performance Testing
[0124] The manganese slag-red mud concrete prepared in Application Examples 1-4 and Comparative Application Examples 1-9 were poured into molds, and the surface was smoothed after 24 hours. The concrete was placed in a curing room for 28 days, and then the compressive strength was tested on the 3rd day (3d) and the 28th day (28d) to evaluate the results.
[0125] The compressive strength test method is carried out in accordance with GB / T 50081-2019, Standard for Experimental Methods of Physical and Mechanical Properties of Concrete.
[0126] The performance test results of the manganese slag-red mud concrete prepared in Application Examples 1-4 and Comparative Application Examples 1-9 are shown in Table 1.
[0127] Table 1: Performance test results of manganese slag-red mud concrete prepared in Application Examples 1-4 and Comparative Application Examples 1-9
[0128] Group 3d compressive strength (MPa) 28d compressive strength (MPa) Application Example 1 28 48 Application Example 2 34 40 Application Example 3 17 49 Application Example 4 32 40 Comparative application example 1 33 37 Comparative Application Example 2 25 38 Comparative Application Example 3 27 36 Comparative Application Example 4 19 29 Comparative Application Example 5 24 38 Comparative Application Example 6 18 27 Comparative Application Example 7 24 30 Comparative Application Example 8 28 38 Comparative Application Example 9 28 41
[0129] It can be seen from Table 1 that the manganese slag-red mud concrete prepared in the present invention has good early strength and late strength, and its 28-day strength exceeds the strength of C40 concrete, indicating that the manganese slag-red mud concrete of the present invention has good strength and durability.
[0130] In Application Example 4, after adjusting the content of red mud, manganese slag and composite activator, the total calcium oxide content increased, while the aluminum oxide and iron oxide contents decreased, resulting in an increase in the content of calcium silicate hydrate and an increase in the 3d strength, while the calcium aluminoferrite and NASH contents decreased, resulting in a decrease in the 28d strength.
[0131] The difference between Application Example 1 and Application Example 2 is that the ratio of cement to mineral powder in the activator is adjusted, so that the active substance is increased, and the calcium hydroxide released by cement hydration is increased. Although the early strength is enhanced, the later strength decreases.
[0132] The difference between Application Example 2 and Application Example 1 is that nano calcium carbonate is not added, which increases the porosity of the system and causes the colloid to lose its attachment medium, resulting in a decrease in both early and late strengths.
[0133] The difference between Application Example 3 and Application Example 1 is that sodium hydroxide is replaced by calcium hydroxide. Since calcium hydroxide is a medium-strong base with lower alkalinity than sodium hydroxide, its ability to dissolve silicon crystals in the manganese slag-red mud system is not as good as sodium hydroxide, and it releases fewer ions, resulting in a decrease in both early and late strength.
[0134] The difference between Application Example 4 and Application Example 1 is that sodium silicate and sodium hydroxide are not added, resulting in insufficient alkali concentration and inability to effectively excite, resulting in a significant decrease in strength.
[0135] The difference between Application Example 5 and Application Example 1 is that nano calcium carbonate is not added, which leads to poor fluidity during the molding process, increased porosity after molding, and decreased strength.
[0136] The difference between Application Example 6 and Application Example 1 is that lime is not added, resulting in a decrease in calcium ions, a decrease in hydrated calcium silicate and ettringite, and a decrease in strength.
[0137] The difference between Application Example 7 and Application Example 1 is that the mass proportion of red mud, manganese slag and activator mixture is reduced, and the amount of sand added is increased, which reduces the hydrate and leads to a decrease in overall strength.
[0138] The difference between Application Example 8 and Application Example 1 is that the mass of the red mud, manganese slag and activator mixture is increased, and the amount of sand added is reduced. The 3d strength has no obvious change, but due to the relatively reduced water ratio, the hydration is insufficient and the hydration space is insufficient, resulting in a decrease in the 28d strength. In addition, the amount of activator increases, and the production cost increases.
[0139] The difference between Application Example 9 and Application Example 1 is that the excessive water content has no obvious effect on the 3d strength, the porosity increases after curing, and the 28d strength decreases.
[0140] In summary, the present invention uses sodium silicate and sodium hydroxide as a compound, and uses nano calcium carbonate or nano silicon powder as a filler, and combines mineral powder, lime, and cement. The components work together to improve the mechanical properties and durability of the concrete prepared after the red mud and manganese slag are reacted. In addition, by mixing red mud and manganese slag in an appropriate proportion, the two solid waste elements complement each other and form polymer ferroalumina, hydrated calcium silicate, and sodium ferroaluminate gel polymer under the action of an alkali activator, which can not only solidify and stabilize the harmful substances in these wastes, but also prepare a new type of building material with excellent mechanical properties, whose 28-day strength exceeds the strength of C40 concrete, and has good durability.
[0141] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A composite activator, characterized in that: Including mineral powder, lime, cement, filler, A component; The filler includes at least one of nano calcium carbonate and nano silicon powder; The A component includes sodium silicate and sodium hydroxide.
2. The composite activator according to claim 1, characterized in that: Calculated by mass percentage, the composite activator includes 37-75% of mineral powder, 0.9-11% of lime, 18-60% of cement, 0.9-5.5% of filler and 0.9-4.5% of component A.
3. The composite activator according to claim 1, characterized in that: In the component A, the mass ratio of the sodium silicate to the sodium hydroxide is (6-8):
3.
4. The method for preparing the composite activator according to any one of claims 1 to 3, characterized in that: The following steps are involved: Each component is taken to form the composite activator.
5. A manganese slag-red mud concrete, characterized in that: The raw materials for preparing the catalyst include red mud, manganese slag, the composite activator described in any one of claims 1 to 3, gravel, sand and water.
6. The manganese slag-red mud concrete according to claim 5, characterized in that: The sum of the masses of the red mud, manganese slag and the composite activator accounts for 14-25% of the total mass of the manganese slag-red mud concrete; and / or, the mass of the gravel accounts for 40-60% of the total mass of the manganese slag-red mud concrete; and / or, the mass of the sand accounts for 18-33% of the total mass of the manganese slag-red mud concrete; and / or, the mass of the water accounts for 5.5-8.5% of the total mass of the manganese slag-red mud concrete.
7. The manganese slag-red mud concrete according to claim 6, characterized in that: The mass ratio of the red mud, manganese slag and the composite activator is (3-5):3:(2-4).
8. The manganese slag-red mud concrete according to claim 6, characterized in that: The stones include stones with a particle size of 5-10 mm and stones with a particle size of greater than 10 mm and less than or equal to 25 mm.
9. The method for preparing manganese slag-red mud concrete according to any one of claims 5 to 8, characterized in that: The following steps are involved: (1) mixing the red mud, manganese slag and composite activator to obtain a mixed powder; (2) Mixing the mixed powder obtained in step (1) with the gravel, sand and water to obtain the manganese slag-red mud concrete.
10. Use of the composite activator according to any one of claims 1 to 3 or the manganese slag-red mud concrete according to any one of claims 5 to 8 in the resource utilization of manganese slag and red mud.